A Pod‐like Core‐Shell Catalyst with High Reduction Performance Under Mild Conditions. Issue 6 (5th January 2022) - Xu, Fagong; Zhan, Feiyang; Zhang, Beibei; Li, Tuanhui; He, Lei; Du, Liting; Luo, Shizhou; Zheng, Baishu; Yun, Ruirui
Abstract: Recent years, tubular structure as the carrier loading nanoparticles has been reported more and more frequently which is synthesized by pyrolysis polyhedral MOFs. However, the construct mechanism has not been referred. Herein, a tubular structure has been designed by calcining modified ZIF‐8 under different temperature to reveal the formation process of tubular carbon from the polyhedron. As a result, a pod‐like core‐shell catalyst of Fe/Fe3 C‐900 has been obtained and exhibits a high activity and excellent substituent tolerance for the reduction of nitro groups under mild conditions. Abstract : A tubular core‐shell catalyst of Fe/Fe3 C‐900 has been designed and synthesized which shows an excellent activity, chemo‐selectivity and stability for the hydrogenation of nitroarenes under mild conditions.